A Case of Gastric Amphicrine Signet-Ring Cell Carcinoma - Hanamatsu, Yuki (Clin Pathol, 2019)
“Amphicrine” (in Greek, amphi- means “both” or “double”) refers to cells that synchronously exhibit the endocrine and exocrine phenotypes. Gastric amphicrine carcinoma is very rare, and only a few case reports are found in the English literature; thus, its pathobiological features remain unclear. Here, we report a case of amphicrine gastric carcinoma. A woman in her sixth decade of life presented with anemia and underwent upper endoscopy, followed by histopathological examination of biopsy specimens. She appeared to have gastric cancer with a tumor measuring 5.0 cm × 4.0 cm in size. Subsequently, the patient underwent total gastrectomy with lymph node dissection. Histopathological examination revealed a poorly cohesive carcinoma that sparsely coexisted with signet-ring cell carcinoma cells with regional lymph node metastasis. Interestingly, synaptophysin immunoreactivity with the coexistence of Alcian blue was found in individual signet-ring cell carcinoma cells. Furthermore, the present amphicrine carcinoma cells immunohistochemically expressed CD44 variant 9, a functional cancer stem cell marker. We believe that the present case findings may support the idea of multipotent stem cells being an origin of amphicrine gastric cancers.